Variação morfológica entre populações insulares e continentais de anuros (amphibia) - Oliveira, Juliete Costa de [UNIFESP] (2016)
The island organisms undergo ecological and evolutionary pressures different from their mainland conspecifics due to reduced area and isolation. As for the body size of animals, gigantism and dwarfism are two standards known to island organisms. These change in body size of island organisms are usually associated with the availability of resources (food or reproductive), the inter or intraspecific competition and the presence / absence of predators. Here, we investigated whether there are differences in morphology between populations of island frogs and their mainland conspecifics in the Brazilian southeastern islands. The target species are: 1) Thoropa taophora, a territorial species that uses freshwater fillets on rocky shores for reproduction, and 2) Haddadus binotatus, a species with direct development. Males and females of T. taophora presented a tendency to gigantism or no difference in body size in relation to the continental conspecifics. Regarding H. binotatus, males tended to dwarfism or no difference in body size in comparison with mainland conspecifics, while females no presented difference in body size in relation to the mainland. Others morphological variables such as leg length and head length varied between populations. Our results suggest that differences in morphology between populations do not appear to be related to the reproductive mode of frogs, but the characteristics of the islands mainly in relation to the availability of breeding sites and the absence of potential predators.